(untitled) (GEON Journal (Management, Organizations and Business), 2017)
The international organizations that are responsible in ensuring the protection of the rights of children, focus their efforts in the eradication of child labor, involving the main stakeholders who have a direct responsibility in the problem: state, business and society. Therefore the aim of this article is to identify the link between the business sectors in the institutional framework for eradicating child labor. Colombia has adopted an institutional framework through which aligns with international conventions that have been signed regarding the eradication of child labor. This document is the result of a documentary and descriptive research, the methodology used had two stages; the first one was a documentary review and the second one took the analysis of the contents. We can identify that the reviewed regulations are aligned with the willingness of the international agreements in Colombia; however, it is not linked directly with the business sector in the struggle and eradication of the child labor, except for the demand to stop hiring children and for the eradication of the worst forms of child labor. Even though, these two elements include the problem of the child labor, they don’t give enough institutional tools to involve one of the most important players in this issue, as are companies.